2012
DOI: 10.1523/jneurosci.0455-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Subventricular Zone Stem/Progenitor Cells Are Notch1-Dependent in Their Active But Not Quiescent State

Abstract: The adult mammalian forebrain contains neural stem/progenitor cells (NSCs) that generate neurons throughout life. As in other somatic stem cell systems, NSCs are proposed to be predominantly quiescent and proliferate only sporadically to produce more committed progeny. However, quiescence has recently been shown not to be an essential criterion for stem cells. It is not known whether NSCs show differences in molecular dependence based on their proliferation state. The subventricular zone (SVZ) of the adult mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
160
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(171 citation statements)
references
References 56 publications
9
160
0
2
Order By: Relevance
“…Although the mammalian SEZ/SGZ and the zebrafish medial pallium, analyzed here, are not directly homologous domains (Salas et al, 2006;Mueller et al, 2011), their NSCs share fundamental characteristics, such as quiescence, glial attributes and gene expression (Adolf et al, 2006). The fact that Notch receptors other than Notch1 must control adult NSC proliferation/activation was recently hypothesized in the mouse based on the different phenotypes of invalidating RBPJk compared with Notch1 (Basak et al, 2012). The conditional ablation of RBPJk in adult neural progenitors of the SEZ and SGZ led to a transient increase in proliferation of NSCs (Ehm et al, 2010) and, to a larger extent, of the TAP population (Ehm et al, 2010;Imayoshi et al, 2010).…”
Section: Research Articlementioning
confidence: 84%
“…Although the mammalian SEZ/SGZ and the zebrafish medial pallium, analyzed here, are not directly homologous domains (Salas et al, 2006;Mueller et al, 2011), their NSCs share fundamental characteristics, such as quiescence, glial attributes and gene expression (Adolf et al, 2006). The fact that Notch receptors other than Notch1 must control adult NSC proliferation/activation was recently hypothesized in the mouse based on the different phenotypes of invalidating RBPJk compared with Notch1 (Basak et al, 2012). The conditional ablation of RBPJk in adult neural progenitors of the SEZ and SGZ led to a transient increase in proliferation of NSCs (Ehm et al, 2010) and, to a larger extent, of the TAP population (Ehm et al, 2010;Imayoshi et al, 2010).…”
Section: Research Articlementioning
confidence: 84%
“…It has been shown that ablation of RBPJK in adult neural stem cells (NSCs) of the SVZ induces a transient increase in neurogenesis but leads in the long term to a permanent depletion of the progenitor pool . Another recent study, using conditional deletion mouse models for Notch1 and RBPJK in adult NSC of the SVZ, has confirmed that loss of functional Notch signaling exhausts the progenitor pool (Basak et al, 2012). This same study indicates a functional separation between Notch1 and RBPJK function and indicates that Notch1 does not regulate the cell fate of quiescent NSCs, which, instead, appears to be under RBPJK regulation, probably through the other heterologous receptors, Notch2 and Notch3.…”
Section: Notch In Postnatal Neurogenesismentioning
confidence: 75%
“…In the mature brain, Notch signaling is additionally implicated in adult neurogenesis of the subventricular zone (SVZ) (Basak et al, 2012;Imayoshi et al, 2010;Nyfeler et al, 2005) and subgranular zone of the hippocampus (SGZ) (Lugert et al, 2010). Neurogenesis, and integration of new born neurons is thought to contribute to olfaction (SVZ) (Sakamoto et al, 2011) and spatial memory (SGZ) (Kempermann and Gage, 2002).…”
Section: Notch In Postnatal Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations